2011
DOI: 10.1007/s11249-011-9881-8
|View full text |Cite
|
Sign up to set email alerts
|

High Lubricity of Re-Doped Fullerene-Like MoS2 Nanoparticles

Abstract: The electrostatic effects in tribological systems have been studied in the past, especially with regards to data storage media. Nanoparticles (NP) of WS 2 and MoS 2 with fullerene-like structure (IF) have been studied in the past and showed very good tribological behavior. Being semiconductors, their electrical properties can be controlled by, e.g., substituting the lattice Mo (W) atoms with Re (n-type conductivity) and Nb (p-type conductivity) atoms. In this study doping of IF-MoS 2 , and to a lesser degree I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…Unlike the IF nano-MoS 2 spheres reported in Refs. [5,6], the MoS 2 layers in the sphere-like nanoparticles formed only partial close structure. Many crystal defects were observed at the brim of MoS 2 nanoparticles.…”
Section: Ball-disk Friction Pairmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the IF nano-MoS 2 spheres reported in Refs. [5,6], the MoS 2 layers in the sphere-like nanoparticles formed only partial close structure. Many crystal defects were observed at the brim of MoS 2 nanoparticles.…”
Section: Ball-disk Friction Pairmentioning
confidence: 99%
“…Previous studies have shown that the lubrication of MoS 2 was dependent on its size and morphology. Nanoscaled MoS 2 (nano-MoS 2 or n-MoS 2 ) particles usually present better properties than bulk microsized 2H-MoS 2 (micro-MoS 2 or m-MoS 2 ) [4][5][6][7]. Thus, much attention was focused on the synthesis and tribological properties of MoS 2 nanoparticles [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Rapoport et al . and Yadgarov et al . showed that the use of the Re‐doped IF‐MoS 2 nanoparticles in PAO oil resulted in a significantly lower coefficient of friction and wear compared with un‐doped IF‐MoS 2 , IF‐WS 2 or 2H‐MoS 2 particles.…”
Section: Discussionmentioning
confidence: 99%
“…One of the purposes of this novel synthesis strategy is linked to the attempt of reducing the agglomeration tendency of the nanoparticles. For example, Rapoport et al and Yadgarov et al 19,20 showed that the use of the Re-doped IF-MoS 2 nanoparticles in PAO oil resulted in a significantly lower coefficient of friction and wear compared with un-doped IF-MoS 2 , IF-WS 2 or 2H-MoS 2 particles. It was reported that Re atoms were acting as electron donors and, therefore, the Re-doped IF-MoS 2 particles should have a negative charge at the surface.…”
Section: Behaviour Of the If-mos 2 Nanoparticles At The Nanoscalementioning
confidence: 99%
“…nanomaterials play an important role in the fabrication of devices like telecommunication and optical components, solid‐state lasers, and many others . Therefore, it is of great interest to develop a facile synthetic method for the synthesis of high‐quality RE‐doped nanomaterials that have uniformity in size and shape . RE‐doped nanoparticles have been suggested as a promising new class of material with properties comparable to those of semiconductor quantum dots and organic dyes and with superior optical and chemical properties …”
Section: Introductionmentioning
confidence: 99%